Appropriate nitrogen application rate with decreased basal/topdressing ratio improves yield, quality, water productivity, and N-use efficiency of forage maize in a rainfed region - Zhongli Li; Wei Gao; Congze Jiang; Yongli Lu; Muhammad Kamran; Xianlong Yang (Agricultural Water Management, 2025)
Crop cultivation in rainfed agricultural regions globally faces the challenges of water scarcity and irrational nitrogen (N) fertilizer application, causing fluctuating yields, reduced N-use efficiency, and increased environmental pollution. A two-year field experiment was conducted from 2021 to 2022 in a typical rainfed region of northwestern China to investigate the effects of four N application rates (0, 90, 180, 270 kg hm−2) and two basal/topdressing ratios (2:8 and 4:6) and their interactions on the growth, dry matter (DM) yield, forage quality, water productivity (WP), and N-use efficiency of forage maize (Zea mays L.). The LAI, DM yield, crude protein (CP) yield, food equivalent unit yield (FEU yield), WPDM, WPCP, WPFEU and aboveground N uptake of forage maize significantly (P < 0.05) increased with the increase in N application rate from 0 to 180 kg hm−2. The soil NO3-N accumulation in 0–200 cm soil layer increased linearly, whereas the partial factor productivity of applied N (PFPN) and N recovery efficiency (REN) decreased linearly with the increase in N rates. The regression analysis further revealed that the DM yield, FEU yield, WPDM, WPFEU, N uptake, PFPN and REN at all N rates were generally higher at 2:8 basal/topdressing ratio compared to 4:6 ratio. The required nitrogen application rates to achieve maximum values for DM yield, FEU yield, WPDM, WPFEU and above-ground N uptake under the 2:8 basal/topdressing ratio were reduced by 3.3 %, 7.3 %, 7.3 %, 9.6 % and 13.8 %, respectively, compared to the 4:6 ratio. Therefore, N application rate of 180 kg hm−2 and basal/topdressing ratio of 2:8 is recommended as a proper N fertilization management for achieving high yield, quality, water productivity, and N-use efficiency of forage maize in northwestern China and areas with similar climatic conditions.